Closest horizons of Hsp70 engagement to manage neurodegeneration - Venediktov, Artem A.; Bushueva, Olga Yu; Kudryavtseva, Varvara A.; Kuzmin, Egor A.; Moiseeva, Aleksandra V.; Baldycheva, Anna; Meglinski, Igor; Piavchenko, Gennadii A. (Frontiers in Molecular Neuroscience, 2023)
The review specifies cue points among extra-abundant data related to multifaceted roles of 70 kilodalton-weighed heat shock proteins (Hsp70) in neurodegeneration. Hsp70 might be significant for neuropharmacology, as the issue has been actively studied since the early 2000s, and clinical trials are encouraging. A cross-section of the current state is required to synchronize efforts. We have launched our own comparative studies of exo-and endogenous heat shock proteins in murine models, and several large projects already do a similar but not the same work. We find it important to feel the heartbeat of the process for all the key actors and that is by publishing in such a widely viewed periodical as Frontiers in Molecular Neuroscience is. Heat shock proteins breakdown barriers between Neuroscience, Immunology, and Oncology. Our concept seeks to integrate the neurobiological and immunological roles of heat shock protein in neurodegeneration. The review would disclose an interesting topic for fundamental studies in neurodegeneration, neuroimmunology, and neurooncology with a laconic but thorough report about contemporary advancements.